The phenomenon of multi-drug resistance in the treatment of malignant tumors - Vtorushin, S.V.; Khristenko, K.Y.; Zavyalova, M.V.; Perelmuter, V.M.; Litviakov, N.V.; Denisov, E.V.; Dulesova, A.Y.; Cherdyntseva, N.V. (Experimental Oncology, 2014)
Multi-drug resistance (MDR) is a condition when there is broad cross-resistance of cells to various agents which are different in structure and effect. Modern perceptions on mechanisms of MDR development in malignant tumors have been considered, in particular, in treating breast cancer. Physiological functions and contribution to MDR development of ABC-transporter protein families have been described. The role of activation of glutathione system enzymes and apoptosis-regulating proteins in MDR formation has been shown. Key Words: multi-drug resistance, ABC-transporters, glutathione system, apoptosis-controlling genes.